IMPROVING MATHEMATICS LEARNING OUTCOMES ON EXPONENTS THROUGH WORDWALL MEDIA FOR STUDENTS OF CLASS X-1 MAN 2 PANDEGLANG - Indriani, Arina Nur; Yayan Miftahul Iman (Cakrawala Pedagogik, 2025)
This study aims to improve mathematics learning outcomes in exponents through the use of Wordwall media for 10th-grade students at MAN 2 Pandeglang. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 30 10th-grade students of MIPA 2. The research instruments consisted of a learning outcome test, student activity observation sheets, and brief interviews. The results showed a significant improvement from the initial conditions to the second cycle. The average student score increased from 65.3 at the initial conditions to 74.1 in the first cycle, and 83.2 in the second cycle. The percentage of students achieving the Minimum Completion Criteria (KKM ? 75) also increased from 30% to 90%. Observations showed an increase in student learning engagement and motivation. Thus, Wordwall media is an effective interactive learning tool for improving mathematics learning outcomes in exponents.